PENGARUH MODEL TARL BERBANTUAN KARTU SUKU KATA TERHADAP KEMAMPUAN MEMBACA AWAL SISWA KELAS II SDN TANGGA - Sri Rezeki Agustina; Nanang Diana; Ihsan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This quasi-experimental study aims to determine the effect of the Teaching at the Right Level (TaRL) model assisted by syllable card media on the early reading literacy ability of second-grade students at SDN Tangga. The research design used was one group pretest-posttest design involving 11 students as samples selected by saturated sampling technique. Data were collected through pretest and posttest of early reading literacy instruments consisting of 25 items covering letter recognition, syllable reading, simple word reading, simple sentence reading, and basic reading comprehension. Data analysis was performed using descriptive statistics and paired sample t-test. The results showed that there was a significant effect of the TaRL model assisted by syllable card media on students' early reading literacy ability with t-count = 9,45 and significance value p = 0,000 < 0,05. The N-gain score obtained was 0,42 in the medium category. These findings indicate that the TaRL model assisted by syllable cards can effectively improve early reading literacy skills in elementary school students through learning that is tailored to the actual ability level of students and supported by concrete media.